Maghza Nasr Hamid Abu Zayd's Interpretation Concept as A Counter of Polygamy Pragmatism - Sam'ani Sam'ani (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The main purpose of this research is to reveal the deep meaning of polygamous verses by using the theoretical approach of Nasr Hamid Abu Zayd's text study. As a critical Islamic thinker, Nasr produced many controversial understandings with classical thinkers, including in interpreting the polygamy verse. Nasr sees the meaning of the verse of polygamy in its historical context as a limitation of the human relationship between men and women in the tradition of pre-Islamic Arab society. This historical origin is only a starting point for understanding the verse, not as the main message of the Qur'an. Nasr photographed the meaning of the verse of polygamy in the context of the Qur'an as a whole. The placement of the text in its comprehensive context produces the original meaning and the meaning of significance (magza) and reveals the hidden dimension of meaning (al maskut 'anhu) namely the principle of monogamy. By revealing this hidden meaning, it will be able to counteract the pragmatic polygamists who are currently happening on the pretext of religion.